Longitudinal impact of sodium-glucose co-transporter-2 versus dipeptidyl peptidase-4 inhibitors on weight and body mass index in type 2 diabetes: a 12-month comparative analysis - Faisal, Syed Raziuddin; H. S., Shekar; Biyabani, Syed Afzal Uddin; Naema, Hafsa (International Journal of Research in Medical Sciences, 2025)
Background: Obesity and elevated body mass index (BMI) are strongly associated with poor glycaemic control and increased cardiometabolic risk in type 2 diabetes mellitus (T2DM). Beyond glycaemic efficacy, contemporary antidiabetic agents are increasingly evaluated for their effects on weight and metabolic outcomes. Sodium-glucose co-transporter-2 (SGLT-2) inhibitors and dipeptidyl peptidase-4 (DPP-4) inhibitors are widely prescribed, yet comparative long-term data on their impact on weight and BMI in Indian populations remain limited. Methods: This 12-month observational study included 200 T2DM patients 100 each receiving SGLT-2 or DPP-4 inhibitors. Assessments were conducted at baseline and at 3, 6, 9, and 12 months. Primary outcomes were changes in body weight and BMI, analysed using SPSS v31.0 with paired t-tests, repeated measures ANOVA, and Bonferroni/Sidak post hoc tests. Statistical significance was set at p<0.05. Results: Patients on SGLT-2 inhibitors exhibited consistent and significant reductions in both parameters: mean body weight declined from 91.61±4.09 kg to 77.63±4.61 kg (Δ=-13.98 kg, p<0.001), and BMI from 29.57±2.68 to 23.13±2.09 (Δ=-6.44, p<0.001). Conversely, DPP-4 users showed negligible changes (Δ=+0.14 kg and -0.10, both p>0.3). The SGLT-2 group’s weight loss was progressive and sustained throughout 12 months. Although gender distribution was similar (p=0.744), younger age in the SGLT-2 group may have influenced outcomes. Conclusions: SGLT-2 inhibitors produced significant, durable reductions in weight and BMI versus DPP-4 inhibitors, highlighting their dual metabolic advantage in comprehensive T2DM management.